2012
DOI: 10.1093/icvts/ivs454
|View full text |Cite
|
Sign up to set email alerts
|

Is home monitoring of international normalised ratio safer than clinic-based monitoring?

Abstract: A best evidence topic was written according to a structured protocol, to answer the question: 'In patients taking warfarin, is home self-monitoring of international normalized ratio (INR) safer than clinic-based testing in reducing bleeding, thrombotic events and death?' Altogether, 268 papers were found using the reported search. Five papers represented the highest level of evidence to answer the clinical question (four systematic reviews with meta-analysis and one meta-analysis). The authors, journal, date a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Home INR testing has been shown to have favorable outcomes in the improvement of TTR. Statistically significant improvements in TTR were found in numerous studies and meta-analyses comparing home testing to clinic-based testing (Cumberworth, Mabvuure, Hallam, & Hindocha, 2013; Heneghan et al, 2016; Matchar et al, 2010; Xu et al, 2012). Even when home-testing patients returned to clinic-based care, they continued to show statistically significant improvements in their TTR compared with the control group (75% vs. 59%, respectively) (Ryan, O'Shea, & Byrne, 2010).…”
Section: Evidence From the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Home INR testing has been shown to have favorable outcomes in the improvement of TTR. Statistically significant improvements in TTR were found in numerous studies and meta-analyses comparing home testing to clinic-based testing (Cumberworth, Mabvuure, Hallam, & Hindocha, 2013; Heneghan et al, 2016; Matchar et al, 2010; Xu et al, 2012). Even when home-testing patients returned to clinic-based care, they continued to show statistically significant improvements in their TTR compared with the control group (75% vs. 59%, respectively) (Ryan, O'Shea, & Byrne, 2010).…”
Section: Evidence From the Literaturementioning
confidence: 99%
“…Improvements in TTR translate into a reduction in adverse events, leading to cost savings and improvements in patient well-being (Lafata, Martin, Kaatz, & Ward, 2000; Phibbs et al, 2016). Home testing has been shown to significantly reduce thromboembolic events (42–55% reduction) and reduce all-cause mortality by 26–42% (Cumberworth et al, 2013). The reduction in major thromboembolism and mortality was confirmed by Bloomfield et al (2011).…”
Section: Evidence From the Literaturementioning
confidence: 99%
“…The target INR that is required in AF patients is between 2 and 3. Home monitoring of INR has proven to reduce the risk of thromboembolism, bleeding event, and death [ 10 ].…”
Section: Warfarinmentioning
confidence: 99%
“…Two options of self-care are available to the patient: patient self-testing (PST), where the INR test is executed by the patient and the INR value is communicated with the patient’s clinic, which responds with a new dosage schedule; and patient self-management (PSM), where the patients are trained to monitor and interpret the INR themselves, and adjust the anticoagulant dose accordingly. Systematic reviews have shown PST and PSM to be superior to standard monitoring, with fewer thromboembolic events, decreased overall mortality and reduced bleeding events [ 7 , 9 12 ]. PST/PSM is therefore recommended in anticoagulant guidelines for suitable patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%